Infected Congenital Epicardial Cyst Presenting as Acute Abdomen. Issue 12 (December 2016) - Dribin, Timothy; Files, Matthew D.; Rudzinski, Erin R.; Kaplan, Ron; Stone, Kimberly P.
Abstract : Abstract: A previously healthy 3-year-old boy presented to the emergency department with abdominal pain, fever, and emesis. Laboratory and radiologic evaluation for causes of acute abdomen were negative; however, review of the abdominal x-ray demonstrated cardiomegaly with the subsequent diagnosis of pericardial cyst by echocardiogram and computed tomography. The patient underwent surgical decompression and attempted removal of the cystic structure revealing that the cyst originated from the epicardium. His abdominal pain and fever resolved postoperatively and he completed a 3-week course of ceftriaxone for treatment of Propionibacterium acnes infected congenital epicardial cyst. Emergency department physicians must maintain a broad differential in patients with symptoms of acute abdomen to prevent complications from serious cardiac or pulmonary diseases that present with symptoms of referred abdominal pain.